Report on Proceedings of the Seventh Annual Meeting of the European CME Forum, London, UK, November 2014. Issue 1 (1st January 2015) - Murray, Ron
Abstract : Participants from three continents attended the Seventh Annual Meeting of the European CME Forum in London between 13 and 14 November 2014. Practical examples of needs assessment and outcomes measurement in CME and continuing professional development (CME-CPD) were provided as well as examples of simulation and virtual patient use in e-learning. Funding options and updates in accreditation and regulatory practice were discussed, and attendees were able to hear the views of education experts, learners in training and representatives of accreditation organisations and commercial supporters. Case studies and panel discussions complemented the invited presentations.